RANGKAP JABATAN KOMISARIS BANK MANDIRI BERDASARKAN UNDANG-UNDANG BADAN USAHA MILIK NEGARA - Dine Qieftiah; Wicaksana, Arif (Faculty of Law, Universitas Trisakti, 2023)
Concurrent positions in BUMN are still a problem, as in the appointment of the Head of the Financial and Development Supervisory Agency (BPKP) as Commissioner of PT. Bank Mandiri (Persero) Tbk. (hereinafter PT. BM). The problem is the appointment of the Head of BPKP as the Board of Commissioners at PT. The BM will cause a conflict of interest in terms of Law No. 19 of 2003 concerning BUMN and what are the legal consequences of concurrent positions on the Board of Commissioners at PT. BM and the Head of BPKP. The research is normative legal research, descriptive, analysed qualitatively, conclusions using deductive logic. The results of research are BPKP conducts audits of BUMN as a whole including PT. BM for this reason, the discussion is about the concurrent position of Muhammad Yusuf Ateh as Commissioner of PT. BM. as well as the Head of the BPKP has the cause a conflict of interest and the legal consequence is his term of office as Commissioner of PT. BM must stop or be deemed to have ended. The conclusion is that the concurrent position creates a conflict of interest and must be terminated or deemed to have ended.